Establishment of emerging practices and research priorities for telerehabilitation in solid organ transplantation: meeting report and narrative literature review - Rozenberg, Dmitry; Logan, Sherrie; Sohrabipour, Sahar; Bourgeois, Nicholas; Cote, Anita; Deliva, Robin; De Souza, Astrid; de Vries, Rienk; Donald, Maoliosa; Ferreira, Manoela; Hart, Donna; Ibrahim Masthan, Megha; et al. (Frontiers in Rehabilitation Sciences, 2025)
Solid organ transplantation (SOT) is a life-saving procedure for those with end-stage organ dysfunction. The main goals of SOT are to improve quality of life and daily function, which are supported by pre- and post-transplant rehabilitation. In-person rehabilitation programs have traditionally been the standard-of-care for delivering rehabilitation for SOT patients. Many programs have adopted a virtual delivery model [telerehabilitation (TR)], an approach that has become increasingly used given restrictions to in-person delivery during the COVID-19 pandemic. Presently, TR programs are being used both clinically and in research with variable practices. A 2-day virtual meeting held in February 2023 brought together over 30 Canadian adult and pediatric researchers, clinicians, and patient and family partners across SOT. The meeting objectives were: (1) To facilitate knowledge exchange and dialogue in TR between patient partners, healthcare professionals, researchers, and key stakeholders, and (2) Identify gaps in clinical practice and research in TR. The discussion focused on delivery methods of TR, digital tools, facilitators and barriers of TR, and the effects of TR on physical and mental health in both adult and pediatric populations. This meeting report incorporates a narrative literature review of SOT and rehabilitation articles in the last 20 years. Future directions in TR are highlighted leading to the development of key research priorities targeted towards improved delivery of TR in SOT patients.